Training on English as a Medium of Instruction: Moroccan Public Secondary School Math and Science Teachers - Anaam, Fatima (International Journal of Language and Literary Studies, 2022)
This study examines the experiences and perceptions of Moroccan public secondary school math and science teachers on training for English as a medium of instruction (EMI). In order to meet this objective, semi-structured interviews were conducted with six EMI math and science teachers from Moroccan public secondary schools in Rabat-Salé-Kénitra. The findings revealed that there was a shortage of training on EMI. All of the EMI teachers did not receive specialized EMI pre-service training. In addition, three undertook a short EMI in-service training, mainly at the beginning of their EMI teaching careers. Additionally, all of these EMI teachers explicitly expressed their need for future training for continuous improvement. Five of them desired additional training in the English language to improve their language proficiency. Three of these five teachers specifically wanted to learn scientific terminologies in English. Furthermore, one of these three teachers wanted to develop her speaking skills to communicate more effectively with students. Differently from the stream, an EMI teacher needed training in both the English language and EMI teaching methodologies. Overall, this study offers insights into this under-researched context of the EMI program in Morocco and provides recommendations for future research.